Method for synthesizing and preparing boron adsorbent for extracting boron from salt lake brine and application thereof
Patent Information
- Application Number
- CN202611243138.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]现有商业化的葡甲胺活性官能团型硼吸附剂,吸附容量低,循环稳定性差,价格高,面对要求大吸附容量的盐湖卤水提硼需求,该商业化的硼吸附树脂不能满足工程化应用的条件
[0085](1)吸附容量优异:硼吸附容量可达59g/L以上,远超现有市售葡甲胺型硼吸附树脂(同等条件下,11g/L),有机无机协同作用,对于卤水提硼具有高吸附容量的优势。
Smart Images

Figure CN122999148A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of boron adsorbent technology, specifically to a method for synthesizing and preparing a boron adsorbent for extracting boron from salt lake brine, and its application. Background Technology
[0002] Boron is an important strategic resource, widely used in new energy, new materials, medicine, glass and ceramics, and salt lake brine is also one of the main sources of boron resources. Currently, the mainstream technologies for boron extraction from salt lakes include solvent extraction, crystallization, membrane separation, single inorganic adsorbent adsorption, and lignin-based adsorption.
[0003] Existing commercially available meglumine active functional group boron adsorbents have low adsorption capacity, poor cycle stability, and high price. Faced with the demand for boron extraction from salt lake brine requiring large adsorption capacity, these commercially available boron adsorption resins cannot meet the conditions for engineering applications.
[0004] Existing lignin-based boron extraction materials generally have major drawbacks: existing patents and literature mostly use water-soluble lignin sulfonate + tannin compound system, the material is highly water-soluble, easily lost, difficult to separate solid and liquid, has poor cycle stability, and relies only on a single phenolic hydroxyl site for adsorption, which cannot be adapted to various boron forms in brine, and there are obvious bottlenecks in adsorption selectivity and capacity.
[0005] Existing inorganic hydroxide materials for boron extraction suffer from several technical shortcomings: conventional amphoteric hydroxides (aluminum hydroxide, chromium hydroxide) exhibit poor acid and alkali stability, easily dissolving and failing under acidic or alkaline conditions; iron-based hydroxides are weakly acid-resistant and prone to phase transitions; bismuth-based hydroxides are easily decomposed in weakly acidic environments and have poor structural stability; furthermore, traditional adsorbents are all single-hydroxyl structures, capable of matching only a single boron species, failing to achieve simultaneous capture of multiple boron species in salt lakes, resulting in low adsorption efficiency. Meanwhile, there is currently no design concept in the industry for composite adsorbents that precisely match multiple boron species through a binary / tri- / quaternary gradient of hydroxyl groups. Summary of the Invention
[0006] The purpose of this invention is to provide a method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine and its application, so as to solve at least one of the technical problems existing in the background art.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine, comprising:
[0009] Weigh organic solvent lignin and sulfate lignin, put them into a high-speed pulverizer to pulverize them, so that the two types of lignin are fully physically mixed; after pulverization, the material is sieved; the sieved mixed lignin is placed in a vacuum drying oven and dried at a constant temperature to remove the free water and low-boiling-point volatile impurities adsorbed in the lignin, and dry composite lignin powder is obtained.
[0010] Dry composite lignin powder was placed in a titanium sulfate solution and stirred to disperse it. Sodium carbonate solution was added dropwise to adjust the pH of the solution to 5-7. The generated metatitanic acid particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, and the filter cake was dried and pulverized to obtain metatitanic acid composite lignin powder.
[0011] Dry composite lignin powder was placed in a lanthanum chloride solution and stirred to disperse it. Sodium carbonate solution was added dropwise to the solution to adjust the pH to 8-9. The resulting lanthanum hydroxide particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, and the filter cake was dried and pulverized to obtain lanthanum hydroxide composite lignin powder.
[0012] The composite lignin powder was placed in a cerium sulfate solution and stirred to disperse it. Sodium hydroxide solution was added dropwise to the solution to adjust the pH value to 9-11. The resulting cerium hydroxide particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried and crushed to obtain cerium hydroxide composite lignin powder.
[0013] Composite lignin powder and polyvinyl butyral were added to dimethylacetamide solvent, heated, and stirred to obtain a uniform organic adhesive.
[0014] Weigh out the metatitanic acid composite lignin powder, lanthanum hydroxide composite lignin powder and cerium hydroxide composite lignin powder and put them into a high-speed rotary granulator to fully mix the three powders physically; add the organic adhesive according to the ratio to granulate and obtain small balls; place the small balls in an oven to evaporate the solvent.
[0015] Epichlorohydrin was mixed and diluted with anhydrous ethanol to obtain a homogeneous solution. The microspheres were placed in a reaction vessel, and the homogeneous solution was added. The reaction was carried out under heat to induce a cross-linking reaction, which caused the epoxy groups in epichlorohydrin to undergo ring-opening etherification with some of the phenolic and alcoholic hydroxyl groups on the molecular chains of lignin and polyvinyl butyral, forming a covalent cross-linked network. The surface and interior of the microspheres were cleaned with deionized water to remove residual epichlorohydrin and ethanol, thus obtaining boron adsorbent microspheres.
[0016] As a further limitation of the first aspect of the present invention, organic solvent lignin and sulfate lignin are weighed in a mass ratio of 1:1-3; the sieved mixed lignin is placed in a vacuum drying oven and dried at a constant temperature of 50-70℃ under the conditions of absolute vacuum degree ≤-0.08 MPa and temperature to remove the adsorbed free water and low boiling point volatile impurities in the lignin, thereby obtaining dried composite lignin powder.
[0017] As a further limitation of the first aspect of the present invention, 1 kg of dry composite lignin powder is placed in 2 L of 1-2 mol / L titanium oxysulfate solution and stirred to disperse. 2-4 mol / L sodium carbonate solution is added dropwise to the solution and the pH of the solution is adjusted to 5-7. The generated metatitanic acid particles are uniformly deposited on the surface of the lignin network.
[0018] As a further limitation of the first aspect of the present invention, 1 kg of dry composite lignin powder is placed in 2 L of 1-2 mol / L lanthanum chloride solution and stirred to disperse. A 2-4 mol / L sodium carbonate solution is added dropwise to the solution, and the pH of the solution is adjusted to 8-9. The generated lanthanum hydroxide particles are uniformly deposited on the surface of the lignin network.
[0019] As a further limitation of the first aspect of the present invention, 1 kg of dry composite lignin powder is placed in 2 L of 1-2 mol / L cerium sulfate solution and stirred to disperse. 2-4 mol / L sodium hydroxide solution is added dropwise to the solution to adjust the pH of the solution to 9-11. The resulting cerium hydroxide particles are uniformly deposited on the surface of the lignin network.
[0020] As a further limitation of the first aspect of the present invention, 1 kg of composite lignin powder and 1-2 kg of polyvinyl butyral with an acetal degree of 40%-45% are added to 20-30 kg of dimethylacetamide (DMAC) solvent, heated to 50-70°C, and stirred for 5-10 h to obtain a uniform organic adhesive.
[0021] As a further limitation of the first aspect of the present invention, metatitanic acid composite lignin powder, lanthanum hydroxide composite lignin powder and cerium hydroxide composite lignin powder are weighed in a mass ratio of 1:1:0.5-1.5.
[0022] As a further limitation of the first aspect of the present invention, the three weighed powders are put into a high-speed rotary granulator and mechanically mixed to ensure that the three powders are fully physically mixed; an organic adhesive is added at a ratio of 0.4-0.6:1 and rotary granulation is carried out.
[0023] As a further limitation of the first aspect of the present invention, epichlorohydrin and anhydrous ethanol are mixed and diluted at a volume ratio of 1:3-5 to obtain a homogeneous solution. 10 kg of small balls are placed in a reaction vessel, and 10-20 kg of homogeneous solution is added. The reaction is carried out at 60-80°C for crosslinking reaction.
[0024] In a second aspect, the present invention provides the application of a boron adsorbent prepared by the preparation method described in the first aspect in boron extraction from salt lake brine, including:
[0025] (1) Adsorption and regeneration process: The prepared boron adsorbent spheres are packed into a fixed bed adsorption column. The brine feed flow rate is controlled at 20-40 BV / h and the adsorption time is 2-3h to dynamically adsorb and enrich boron. After adsorption saturation, a hydrochloric acid solution with a concentration of 0.5-2.5mol / L is used as a regenerator. The regeneration flow rate is 5-15 BV / h and the regeneration time is 1-2h to complete the desorption of boron and the regeneration of the adsorbent. The regenerated adsorbent is directly recycled for the next round of brine boron extraction without additional activation treatment. This process yields an eluent with a concentration of 20-40g / L.
[0026] (2) Evaporation and concentration process: The eluent is placed in a triple-effect evaporator for evaporation and crystallization. The evaporation temperature is 90-110℃ and the evaporation time is 3-5h. The water and hydrogen chloride gas are evaporated and condensed and recovered by a condensation device to obtain hydrochloric acid solution for reuse as a regenerator. This process yields a concentrated solution of 200-250g / L.
[0027] (3) Cooling and crystallization process: The concentrated liquid is slowly cooled from high temperature at a rate of 4-10℃ / h; the solid-liquid mixture is centrifuged and the solid is dried in an oven at 40-50℃ to obtain boric acid crystals. The mother liquor can be recycled.
[0028] The beneficial effects of this invention are as follows: Based on an innovative mechanism that precisely matches different boron species with varying numbers of hydroxyl groups, this invention enables highly selective adsorption of multiple boron species simultaneously and accurately. The boron adsorbent of this invention can be recycled multiple times with a low rate of adsorption capacity reduction. It provides high-density hydroxyl anchoring points and good dispersibility, as well as rigid framework support and structural stability. These two advantages complement each other, forming a "flexible-rigid" synergistic organic framework structure, which is beneficial for improving adsorption capacity and cycle stability.
[0029] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and will become apparent from the description or may be learned by practice of the invention. Attached Figure Description
[0030] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a flowchart illustrating the preparation process of the boron adsorbent described in an embodiment of the present invention.
[0032] Figure 2 This is a flowchart illustrating the process of extracting boron from brine using a boron adsorbent, as described in an embodiment of the present invention.
[0033] Figure 3 This is a physical image of the boron adsorbent microspheres prepared according to Example 1 of the present invention.
[0034] Figure 4 This is a SEM image of the boron adsorbent microspheres prepared according to Example 1 of the present invention.
[0035] Figure 5 This is a photograph of the boron adsorbent microspheres prepared according to Example 2 of the present invention.
[0036] Figure 6 This is a SEM image of the boron adsorbent microspheres prepared according to Example 2 of the present invention.
[0037] Figure 7 This is a physical image of the boron adsorbent microspheres prepared according to Example 3 of the present invention.
[0038] Figure 8 This is a SEM image of the boron adsorbent microspheres prepared according to Example 3 of the present invention. Detailed Implementation
[0039] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0040] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0041] It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with their meanings in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless defined as here.
[0042] Those skilled in the art will understand that, unless specifically stated otherwise, the singular forms “a,” “an,” “the,” and “the” used herein may also include the plural forms. It should be further understood that the term “comprising” as used in this specification means the presence of the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, and / or groups thereof.
[0043] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of those different embodiments or examples.
[0044] To facilitate understanding of the present invention, the present invention will be further explained and described below with reference to the accompanying drawings and specific embodiments. However, the specific embodiments do not constitute a limitation on the embodiments of the present invention.
[0045] Those skilled in the art should understand that the accompanying drawings are merely schematic diagrams of embodiments, and the components in the drawings are not necessarily essential for implementing the present invention.
[0046] Boron exists in six main forms in brine: B(OH)3, B(OH)4 - B3O3(OH)4 - B3O3(OH)5 2- B4O5(OH)4 2- B5O6(OH)4 - Among these boron species, there are neutral molecules and ions with different charges and physical volumes. Ordinary adsorbent materials are difficult to use for adsorbing multiple boron species. This invention addresses the issue of multiple boron species present in brine by employing an innovative mechanism of precisely matching different boron species with varying numbers of hydroxyl groups [metitamin A (dihydroxyl), lanthanum hydroxide (trihydroxy), cerium hydroxide (tetrahydroxy)], combined with the synergistic effect of two compounded lignin and polyvinyl butyral binders. This achieves highly selective adsorption of multiple boron species simultaneously and precisely using a single adsorbent, significantly improving the efficiency of boron extraction from salt lake brine. This boron adsorbent possesses advantages such as acid and alkali resistance, high salt tolerance, high adsorption capacity, high selectivity, and high cycle stability.
[0047] This invention provides a method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine. The preparation of the boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres includes seven steps: "Preparation of composite lignin OK-Lignin", "Preparation of TiO(OH)2-OK-Lignin", "Preparation of La(OH)3-OK-Lignin", "Preparation of Ce(OH)4-OK-Lignin", "Preparation of OK-Lignin-PVB organic adhesive", "Preparation of TiO(OH)2-OK-Lignin", "Preparation of TiO ... The preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres and the preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were carried out through seven steps. This resulted in a boron-extracting adsorbent that is completely insoluble in water, resistant to acids and alkalis, resistant to high salt concentrations, has high adsorption capacity, high selectivity, and high cycling stability. It possesses a dihydroxy-trihydroxy-tetrahydroxy gradient coordination adsorption system and can simultaneously and efficiently capture neutral boric acid molecules, monoboronate ions, and polyboron anions in salt lake brine. Figure 1 As shown, the method specifically includes the following steps:
[0048] (1) Preparation of composite lignin OK-Lignin: Organic solvent lignin (O-Lignin) and sulfate lignin (K-Lignin) were weighed at a mass ratio of 1:1-3. The weighed O-Lignin and K-Lignin lignin powders were put into a high-speed pulverizer and mechanically pulverized at 3000-5000 rpm for 5-10 minutes to ensure that the two lignins were fully physically mixed. The pulverized material was passed through a 100-mesh standard sieve (sieve hole diameter 0.150 mm), and the sieve material was collected for later use. The sieved mixed lignin was placed in a vacuum drying oven and dried under the conditions of absolute vacuum degree ≤-0.08 MPa and temperature 50-70℃ (in this invention, a low vacuum degree of absolute vacuum degree ≤-0.08 MPa is selected, which is beneficial to reduce the boiling point of the liquid and increase the evaporation rate of the liquid; the temperature of 50-70℃ ensures that the liquid can boil and evaporate under this vacuum degree, and this temperature range can ensure that the functional groups of the mixed lignin are not destroyed by high temperature, thus ensuring its chemical properties). The lignin was dried at a constant temperature for 4-6 hours to remove adsorbed free water and low-boiling-point volatile impurities, resulting in dried OK-Lignin powder.
[0049] Organic solvent lignin (O-Lignin), extracted by organic solvent methods, has a relatively low molecular weight (Mw 1000-3000 Da), a high content of phenolic hydroxyl groups (approximately 3.5-5.0 mmol / g), and is rich in guaiac and syringyl structural units. It exhibits good flexibility and is easily dispersed in alkaline media, providing numerous uniform anchoring sites for inorganic nanoparticles. Sulfate lignin (K-Lignin), obtained as a byproduct of sulfate pulping, has a higher molecular weight (Mw 3000-8000 Da), contains more condensed structural units and aliphatic hydroxyl groups, and exhibits greater rigidity, providing excellent mechanical strength and structural stability for the composite adsorbent. When O-Lignin and K-Lignin are combined, O-Lignin provides high-density hydroxyl anchoring sites and good dispersibility, while K-Lignin provides rigid framework support and structural stability. The complementary advantages of both form a synergistic "flexible-rigid" organic framework structure, which is beneficial for improving adsorption capacity and cycling stability.
[0050] Therefore, by weighing organic solvent lignin (O-Lignin) and sulfate lignin (K-Lignin) at a mass ratio of 1:1-3, this invention can obtain high-density hydroxyl anchoring sites and excellent mechanical strength and structural stability. The determination of this ratio range (O-Lignin 25%-50%, K-Lignin 50%-75%) is based on the principle of maximizing the complementary and synergistic functional properties of the two lignins.
[0051] First, the proportion of O-Lignin should not be too high (not exceeding 50%, i.e., the ratio should not be less than 1:1):
[0052] While O-Lignin possesses high phenolic hydroxyl content (3.5-5.0 mmol / g) and excellent dispersibility, its low molecular weight (Mw 1000-3000 Da), short molecular chain, and insufficient rigidity mean that if the proportion of O-Lignin exceeds 50% (e.g., in a ratio below 1:1, O-Lignin becomes the main phase), then:
[0053] Decreased mechanical strength: Low molecular weight O-Lignin cannot form a sufficiently dense and rigid network skeleton, resulting in reduced overall strength of the composite material, which is prone to breakage or structural collapse during subsequent molding or use.
[0054] Insufficient thermal stability: The low molecular weight of O-Lignin makes it more prone to thermal flow and structural rearrangement during drying or heat treatment, which is not conducive to the structural stability of the material.
[0055] Decreased economic viability: The cost of O-Lignin prepared by the organic solvent method is usually higher than that of K-Lignin prepared by the sulfate method, and an excessively high proportion of O-Lignin will significantly increase the cost of raw materials.
[0056] Secondly, the proportion of K-Lignin should not be too high (not exceeding 75%, i.e., the ratio should not exceed 1:3).
[0057] K-Lignin possesses a high molecular weight (Mw 3000-8000 Da) and a rigid condensation structure, providing excellent mechanical strength. However, if the K-Lignin content exceeds 75% (e.g., a ratio greater than 1:3, where K-Lignin becomes the absolute host phase), then:
[0058] Insufficient active site density: The phenolic hydroxyl content of K-Lignin (approximately 1.5-2.5 mmol / g) is much lower than that of O-Lignin. Excessive increase in the proportion of K-Lignin will dilute the hydroxyl anchoring sites of the system, resulting in a decrease in adsorption capacity.
[0059] Poor dispersibility: K-Lignin is less dispersible in alkaline media than O-Lignin. An excessively high proportion of K-Lignin makes it difficult for the composite system to be uniformly dispersed in aqueous or alkaline systems, affecting the uniform loading of inorganic nanoparticles.
[0060] Loss of flexibility: The high-rigidity K-Lignin skeleton lacks the buffer of flexible segments, which increases the brittleness of the composite material and is not conducive to the structural stability during long-term cyclic use.
[0061] Thirdly, the synergistic effect in the 1:1-3 ratio range.
[0062] When the mass ratio of O-Lignin to K-Lignin falls within the range of 1:1 to 1:3:
[0063] A balance is achieved between the continuity of the backbone and the distribution of active sites: K-Lignin forms a continuous rigid backbone, while O-Lignin is uniformly distributed within the backbone as a "filler" or "surface modification." The two interpenetrate each other to form an interpenetrating network structure. The abundant phenolic hydroxyl groups of O-Lignin are densely arranged on the surface and in the internal channels of the backbone, providing a high density of anchoring sites.
[0064] The hydroxyl density remains at a high level: calculated at a 1:3 ratio, the weighted phenolic hydroxyl content of the mixed lignin is approximately (1×4.0 + 3×2.0) / 4 = 2.5 mmol / g, which is still significantly higher than that of K-Lignin alone (2.0 mmol / g). Calculated at a 1:1 ratio, the mixed phenolic hydroxyl content is approximately 3.0 mmol / g. This range ensures that the hydroxyl density remains at a medium-to-high level.
[0065] Optimal balance between mechanical strength and adsorption capacity: The K-Lignin framework provides structural support, while the O-Lignin flexible segments provide stress buffering. Together, they enable the composite material to possess both high strength and good toughness.
[0066] (2) Preparation of TiO(OH)2-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1-2 mol / L titanium oxysulfate TiOSO4 solution and stirred for 10-30 min. 2-4 mol / L sodium carbonate solution was added dropwise to the solution, and the pH of the solution was adjusted to 5-7. The in-situ formation mechanism of metatitanic acid: Ti 4+ + 4OH - → Ti(OH)4 → TiO(OH)2↓ + H2O, the generated metatitanic acid is uniformly deposited on the surface of the lignin network as nano-sized particles. The mixture is filtered, the filter cake is washed with deionized water, and the filter cake is dried at 50-70℃ and then pulverized to obtain TiO(OH)2-OK-Lignin powder.
[0067] In this invention, under the condition that the concentration of the titanium oxysulfate TiOSO4 solution is 1-2 mol / L, in order to control the mass ratio of OK-Lignin powder to synthesized TiO(OH)2, and under the condition of controlling the volume of 2L, the concentration of the titanium oxysulfate TiOSO4 solution needs to be selected as 1-2 mol / L. In addition, this concentration is appropriate, which can avoid the phenomenon of low production efficiency due to the concentration being too low, and can avoid the problems of excessively large particle size, excessively small specific surface area, and uneven reaction caused by the concentration being too high. Choosing a sodium carbonate solution of 2-4 mol / L is recommended. This higher concentration reduces the volume of sodium carbonate solution used and improves the efficiency of solid-liquid separation in the subsequent mixture. If the concentration is too low, the volume of the mixture will be very large, increasing the workload of solid-liquid separation and making it unsuitable for industrialization. Under pH conditions of 5-7, titanium ions can be efficiently hydrolyzed into metatitanic acid with small particle size and large specific surface area. If the pH is too low, the hydrolysis rate will be too slow, making it difficult to industrialize. If the pH is too high, the hydrolysis rate will be too fast, easily forming metatitanic acid with large particle size and small specific surface area.
[0068] (3) Preparation of La(OH)3-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1-2 mol / L lanthanum chloride LaCl3·7H2O solution and stirred for 10-30 min. 2-4 mol / L sodium carbonate solution was added dropwise to the solution, and the pH of the solution was adjusted to 8-9. The in-situ formation mechanism of lanthanum hydroxide: La 3+ + 3OH -→ La(OH)3 ↓, the generated La(OH)3 is uniformly deposited on the surface of the lignin network as nano-sized particles. The mixture is filtered, the filter cake is washed with deionized water, and the filter cake is dried at 50-70℃ and then pulverized to obtain La(OH)3-OK-Lignin powder.
[0069] In this invention, under the condition that the concentration of lanthanum chloride LaCl3·7H2O solution is 1-2 mol / L, in order to control the mass ratio of OK-Lignin powder to synthesized La(OH)3, it is necessary to select 1 kg corresponding to 2 L. Since the volume of 2 L has already been controlled, to further control the mass ratio of OK-Lignin powder to synthesized La(OH)3, a concentration of 1-2 mol / L is required. Furthermore, this concentration is moderate, avoiding the phenomenon of low production efficiency due to excessively low concentration, and also avoiding the phenomenon of excessively large particle size and excessively small specific surface area of the product due to excessively high concentration. To address the problem of uneven reaction, a sodium carbonate solution of 2-4 mol / L is chosen. This higher concentration reduces the volume of sodium carbonate solution used and improves the efficiency of solid-liquid separation in the subsequent mixture. If the concentration is too low, the volume of the mixture will be very large, increasing the workload of solid-liquid separation and making it unsuitable for industrialization. Under pH conditions of 8-9, lanthanum ions can be efficiently hydrolyzed into lanthanum hydroxide with small particle size and large specific surface area. If the pH is too low, the hydrolysis rate is too slow, making it difficult to industrialize. If the pH is too high, the hydrolysis rate is too fast, easily forming La(OH)3 with large particle size and small specific surface area.
[0070] (4) Preparation of Ce(OH)4-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1-2 mol / L cerium-rich Ce(SO4)2 solution and stirred for 10-30 min. 2-4 mol / L sodium hydroxide solution was added dropwise to the solution to adjust the pH to 9-11. The in-situ formation mechanism of cerium hydroxide: Ce 4+ + 4OH - → Ce(OH)4 ↓, the generated Ce(OH)4 is uniformly deposited on the surface of the lignin network as nano-sized particles. The mixture is filtered, the filter cake is washed with deionized water, and the filter cake is dried at 50-70℃ and then pulverized to obtain Ce(OH)4-OK-Lignin powder.
[0071] In this invention, under the condition that the concentration of cerium persulfate Ce(SO4)2 solution is 1-2 mol / L, in order to control the mass ratio of OK-Lignin powder to synthesized La(OH)3, it is necessary to select 1 kg corresponding to 2 L. Since the volume of 2 L has been controlled, in order to control the mass ratio of OK-Lignin powder to synthesized Ce(OH)4, a 1-2 mol / L cerium persulfate Ce(SO4)2 solution is required. Furthermore, this concentration is moderate, avoiding the phenomenon of low production efficiency due to excessively low concentration, and also avoiding the particle size distribution of the product due to excessively high concentration. To address the problems of excessively large particle size, small specific surface area, and uneven reaction, a sodium hydroxide solution of 2-4 mol / L is selected. This higher concentration can reduce the volume of sodium hydroxide solution used and improve the efficiency of solid-liquid separation in the subsequent mixture. If the concentration is too low, the volume of the mixture will be very large, increasing the workload of solid-liquid separation. Under the condition of pH 9-11, cerium ions can be efficiently hydrolyzed into cerium hydroxide with small particle size and large specific surface area. If the pH is too low, the hydrolysis rate is too slow, making it difficult to industrialize. If the pH is too high, the hydrolysis rate is too fast, easily forming cerium hydroxide with large particle size and small specific surface area.
[0072] (5) Preparation of OK-Lignin-PVB organic adhesive: Add 1 kg of OK-Lignin powder and 1-2 kg of polyvinyl butyral with an acetal degree of 40%-45% to 20-30 kg of dimethylacetamide (DMAC) solvent, heat to 50-70℃, stir for 5-10 h to obtain a uniform OK-Lignin-PVB-DMAC organic adhesive.
[0073] In this invention, the reason for selecting 1kg of OK-Lignin powder corresponding to the range of 1-2kg is that the main function of the adhesive is to bind and stick the powder together. In comparison, PVB has a better binding effect, while OK-Lignin has a slightly weaker binding effect. In order to ensure the mechanical strength of the particles after molding, more PVB is needed and less OK-Lignin is needed. When formulating organic adhesives, in addition to using PVB as a core component, OK-Lignin is also added as a core component. The beneficial effects of using OK-Lignin plus PVB dual adhesives are as follows: adding extra OK-Lignin to the organic adhesive, with OK-Lignin mainly functioning as an adhesive, will not occupy the OK-Lignin in the three core components of TiO(OH)2-OK-Lignin, La(OH)3-OK-Lignin, and Ce(OH)4-OK-Lignin. This helps maintain the binding stability and interaction force between TiO(OH)2, La(OH)3, and Ce(OH)4 and OK-Lignin in the three core components of TiO(OH)2-OK-Lignin, La(OH)3, and Ce(OH)4-OK-Lignin, ensuring the dispersibility and adsorption performance of the three effective components of TiO(OH)2, La(OH)3, and Ce(OH)4. Polyvinyl butyral with an acetal content of 40%-45% is used, which belongs to low-acetal PVB. This molecular structure contains a large number of hydroxyl groups, which have two main functions. First, they can adsorb boron, acting as an adhesive while also improving boron extraction, thus increasing the total boron extraction capacity of the boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres. Second, they can chemically crosslink with epichlorohydrin (ECH) together with lignin, using ECH to chemically crosslink PVB and lignin to form a more stable spatial network organic framework structure, ensuring that the microspheres have high mechanical strength and high porosity. Since both OK-Lignin and PVB need to be dissolved in DMAC solvent, choosing a solvent amount of 20-30 kg can result in an adhesive with low viscosity and a high solid content of effective binder. If the solvent amount is too small, the adhesive viscosity will be very high, resulting in poor flowability and hindering production operations. If the solvent amount is too large, the effective binder solid content of the adhesive will be very low, leading to very poor mechanical strength of the molded particles during the molding process.
[0074] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: Weigh TiO(OH)2-OK-Lignin, La(OH)3-OK-Lignin and Ce(OH)4-OK-Lignin in a mass ratio of 1:1:0.5-1.5. Put the weighed powders into a high-speed rotary granulator and mechanically mix them at 1000-2000 rpm for 10-20 min to ensure that the powders are fully physically mixed. Then, OK-Lignin-PVB-DMAC adhesive was added at a ratio of 0.4-0.6:1, and high-speed rotary granulation was carried out at 500-1000 rpm for 8-16 minutes to obtain small balls with a particle size of 0.7-1.5 mm. After evaporating the DMAC solvent in an oven at 40-60℃, TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB small balls were obtained.
[0075] In this invention, a mass ratio of 1:1:0.5-1.5 is chosen because all three active ingredients play a crucial role in the extraction of boron species. This ratio allows for the extraction of multiple boron species from the salt lake system. Metatitanic acid (TiO(OH)2, 2 hydroxyl groups): structurally stable and resistant to acids and alkalis, it precisely matches the small-molecule neutral boric acid H3BO3 in the salt lake, forming a stable five-membered ring complex, achieving efficient capture of small-molecule boron; Lanthanum hydroxide (La(OH)3, 3 hydroxyl groups): a highly acid and alkali resistant rare earth hydroxide with a stable three-hydroxyl stereocoagulation structure, precisely matching the mono-polyboronate B(OH)4. - This significantly enhances the selective adsorption capacity of monoboron; cerium hydroxide (Ce(OH)4, with four hydroxyl groups): its tetrahydroxy multi-site structure exhibits strong coordination ability, specifically suited to polymeric polyboron anions, achieving stable adsorption of macromolecular polyboron through multi-point cross-linking. Too much adhesive leads to excessively wet powder after mixing, causing agglomeration into a dough-like consistency, resulting in granulation failure; too little adhesive results in insufficient adhesive around the powder, preventing agglomeration into target particles and lower mechanical strength. Therefore, an adhesive-to-powder ratio of 0.4-0.6:1 is selected.
[0076] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Epichlorohydrin (ECH) and anhydrous ethanol were mixed and diluted at a volume ratio of 1:3-5 to obtain a homogeneous solution. 10 kg of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres were placed in a reaction vessel, and 10-20 kg of ECH ethanol solution was added. The cross-linking reaction was carried out at 60-80℃ for 3-5 h, so that the epoxy groups of ECH and some phenolic hydroxyl and alcohol hydroxyl groups on the lignin and PVB molecular chains underwent ring-opening etherification reaction to form a covalent cross-linked network. The surface and interior of the microspheres were cleaned with deionized water to remove residual ECH and ethanol, and TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were obtained.
[0077] In this invention, epichlorohydrin (ECH) and anhydrous ethanol are mixed at a volume ratio of 1:3-5. The rate and quantity of the ring-opening etherification reaction between ECH and some of the phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains are carefully controlled. The reaction rate must not be too fast or too slow, and the remaining quantity of phenolic and alcoholic hydroxyl groups must be ensured; the amount reacted must not be too small or too large. If the ECH concentration is too high, the subsequent ring-opening etherification reaction with some of the phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains will be too fast and excessive, resulting in a significant reduction in the number of phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains, which is inconsistent with the intent of this patent. If the ECH concentration is too low, the subsequent ring-opening etherification reaction with some of the phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains will be too slow and the amount reacted will be too small, resulting in the inability to form a covalent cross-linked network or a network that is too loose. The goal is to select 10 kg of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres, with a mass ratio of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres to ECH ethanol solution of 1:1-2. This is to facilitate the ring-opening etherification reaction between the epoxy groups of ECH and some phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains, forming a covalent cross-linked network, and thus obtaining a suitable reaction rate and a suitable number of phenolic and alcoholic hydroxyl groups undergoing ring-opening etherification. Add 10-20 kg of ECH ethanol solution. The goal is to achieve a mass ratio of 1:1-2 between the TiO(OH)₂-La(OH)₃-Ce(OH)₄-OK-Lignin-PVB microspheres and the ECH ethanol solution. This ratio facilitates the ring-opening etherification reaction between the epoxy groups of ECH and some phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains, forming a covalent cross-linked network. This results in a suitable reaction rate and an appropriate number of phenolic and alcoholic hydroxyl groups undergoing ring-opening etherification. Maintaining the cross-linking reaction at 60-80℃ is also beneficial. Too low a temperature results in a slow or non-existent reaction; too high a temperature leads to an excessively fast reaction, making it difficult to control the number of functional groups involved.
[0078] Boron exists in six main forms in brine: B(OH)3, B(OH)4 - B3O3(OH)4 - B3O3(OH)5 2- B4O5(OH)4 2- B5O6(OH)4 -Among these boron species, there are neutral molecules and ions with different charges, and their physical volumes also differ. Ordinary adsorbent materials struggle to adsorb multiple boron species simultaneously. This invention addresses the issue of multiple boron species present in brine by precisely matching different boron species [metatinic acid (dihydroxy), lanthanum hydroxide (trihydroxy), cerium hydroxide (tetrahydroxy)] with varying numbers of hydroxyl groups. Combined with the synergistic effect of two compounded lignin and polyvinyl butyral binders, this invention achieves highly selective adsorption, enabling the adsorbent to simultaneously and precisely capture multiple boron species, significantly improving the efficiency of boron extraction from salt lake brine.
[0079] The boron adsorbent's chemical composition utilizes inorganic components containing dihydroxy metatitanic acid, trihydroxy lanthanum hydroxide, and tetrahydroxy cerium hydroxide, rather than a single-species inorganic component. Metatitanic acid (TiO(OH)2, 2 hydroxyl groups): structurally stable and resistant to acids and alkalis, precisely adapts to small-molecule neutral boric acid H3BO3 in salt lakes, forming a stable five-membered ring complex for efficient capture of small-molecule boron. Lanthanum hydroxide (La(OH)3, 3 hydroxyl groups): a highly acid and alkali resistant rare earth hydroxide with a stable trihydroxy stereocoagulation structure, precisely adapts to monopolyboronate B(OH)4. - This significantly enhances the selective adsorption capacity of monoboron; cerium hydroxide (Ce(OH)4, with four hydroxyl groups): its tetrahydroxy multi-site structure exhibits strong coordination ability, specifically suited to high-molecular-weight polyboron anions, achieving stable adsorption of macromolecular polyboron through multi-site cross-linking. A 2 / 3 / 4-membered gradient hydroxyl synergistic system is constructed, comprehensively covering the adsorption of all boron species in salt lakes, completely overcoming the technical bottleneck of traditional adsorbents that can only adsorb a single boron species. It breaks through the upper limits of adsorption capacity and selectivity caused by traditional single-site adsorbents, and all components are resistant to the acid-alkali and high-salt environments of salt lakes, exhibiting extremely strong structural stability and significantly improving adsorption capacity and selectivity.
[0080] In this invention, such as Figure 2 As shown, a method for extracting boron from salt lake brine using the above-mentioned adsorbent is also provided, comprising the following steps:
[0081] (1) Adsorption and regeneration process: The prepared boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were packed into a fixed-bed adsorption column. The brine feed flow rate was controlled at 20-40 BV / h, and the adsorption time was 2-3h to dynamically adsorb and enrich boron. After adsorption saturation, a hydrochloric acid solution with a concentration of 0.5-2.5 mol / L was used as a regenerator. The regeneration flow rate was 5-15 BV / h, and the regeneration time was 1-2h to complete the desorption of boron and the regeneration of the adsorbent. The regenerated adsorbent was directly recycled for the next round of brine boron extraction without additional activation treatment. This process yielded an eluent with a concentration of 20-40 g / L.
[0082] (2) Evaporation and concentration process: The eluent is placed in a triple-effect evaporator for evaporation and crystallization. The evaporation temperature is 90-110℃ and the evaporation time is 3-5h. Water and hydrogen chloride gas are evaporated and then condensed and recovered through a condenser to obtain hydrochloric acid solution for reuse as a regenerator. This process yields a concentrated solution of 200-250g / L.
[0083] (3) Cooling and crystallization process: The concentrated liquid is slowly cooled from high temperature at a rate of 4-10℃ / h (too fast a cooling rate will form fine crystals, increasing the difficulty of solid-liquid separation). The solid-liquid mixture is centrifuged and the solid is dried in an oven at 40-50℃ to obtain boric acid crystals. The mother liquor can be recycled.
[0084] The boron adsorbent of the present invention has the following core advantages:
[0085] (1) Excellent adsorption capacity: The boron adsorption capacity can reach more than 59 g / L, which is far greater than the existing commercially available meglumine type boron adsorption resin (11 g / L under the same conditions). The synergistic effect of organic and inorganic has the advantage of high adsorption capacity for boron extraction from brine.
[0086] (2) Boron has extremely high selectivity: there are six main forms of boron in brine: B(OH)3, B(OH)4 - B3O3(OH)4 - B3O3(OH)5 2- B4O5(OH)4 2- B5O6(OH)4 - To address the various boron species present in brine, this invention utilizes an innovative mechanism based on the precise matching of different hydroxyl groups to different boron species [metitamin A (dihydroxy), lanthanum hydroxide (trihydroxy), cerium hydroxide (tetrahydroxy)], achieving highly selective adsorption of multiple boron species simultaneously and precisely.
[0087] (3) Excellent cycle stability: The boron adsorbent of the present invention only decreases by 1.4% after 300 cycles, which is much lower than the existing commercially available meglumine type boron adsorbent resin (under the same conditions, the adsorption capacity decreases by 37.2%).
[0088] Example 1
[0089] In this embodiment 1, a method for synthesizing boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres is provided. The synthesis method includes the following steps:
[0090] (1) Preparation of composite lignin OK-Lignin: Organic solvent lignin (O-Lignin) and sulfate lignin (K-Lignin) were weighed at a mass ratio of 1:1. The weighed O-Lignin and K-Lignin lignin powders were put into a high-speed pulverizer and mechanically pulverized at 3000 rpm for 5 min to ensure thorough physical mixing of the two lignins. The pulverized material was passed through a 100-mesh standard sieve (sieve hole diameter 0.150 mm), and the sieved material was collected for later use. The sieved mixed lignin was placed in a vacuum drying oven and dried at an absolute vacuum of ≤-0.08 MPa and a temperature of 50℃ for 4 h to remove adsorbed free water and low-boiling-point volatile impurities from the lignin, resulting in dried OK-Lignin powder.
[0091] (2) Preparation of TiO(OH)2-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1 mol / L titanium oxysulfate (TiOSO4) solution and stirred for 10 min. 2 mol / L sodium carbonate solution was added dropwise to the solution to adjust the pH to 5. The generated metatitanic acid was uniformly deposited on the surface of the lignin network as nano-sized particles. The mixture was filtered, the filter cake was washed with deionized water, dried at 50 °C, and then pulverized to obtain TiO(OH)2-OK-Lignin powder.
[0092] (3) Preparation of La(OH)3-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1 mol / L lanthanum chloride LaCl3·7H2O solution and stirred for 10 min. 2 mol / L sodium carbonate solution was added dropwise to the solution to adjust the pH to 8. The generated La(OH)3 particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried at 50 °C, and then pulverized to obtain La(OH)3-OK-Lignin powder.
[0093] (4) Preparation of Ce(OH)4-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1 mol / L cerium-rich Ce(SO4)2 solution and stirred for 10 min. 2 mol / L sodium hydroxide solution was added dropwise to the solution to adjust the pH to 9. The generated Ce(OH)4 particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried at 50 °C, and then pulverized to obtain Ce(OH)4-OK-Lignin powder.
[0094] (5) Preparation of OK-Lignin-PVB organic adhesive: 1 kg of OK-Lignin powder and 1 kg of polyvinyl butyral with an acetal degree of 40%-45% were added to 20 kg of dimethylacetamide (DMAC) solvent, heated to 50°C, and stirred for 5 h to obtain a uniform OK-Lignin-PVB-DMAC organic adhesive.
[0095] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: TiO(OH)2-OK-Lignin, La(OH)3-OK-Lignin, and Ce(OH)4-OK-Lignin were weighed in a mass ratio of 1:1:0.5. The three powders were put into a high-speed rotary granulator and mechanically mixed at 1000 rpm for 10 min to ensure thorough physical mixing. Then, OK-Lignin-PVB-DMAC adhesive was added at a glue-to-powder ratio of 0.4:1 and granulated at 500 rpm for 8 min to obtain microspheres with a particle size of 0.7-1.5 mm. The microspheres were placed in a 40℃ oven to evaporate the DMAC solvent, resulting in TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres.
[0096] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Epichlorohydrin (ECH) and anhydrous ethanol were mixed and diluted at a volume ratio of 1:3 to obtain a homogeneous solution. 10 kg of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres were placed in a reaction vessel, and 10 kg of ECH ethanol solution was added. The reaction was carried out at 60 °C for 3 h to allow the epoxy groups of ECH to undergo ring-opening etherification with some phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains, forming a covalent cross-linked network. The surface and interior of the microspheres were cleaned with deionized water to remove residual ECH and ethanol, thus obtaining TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres.
[0097] In this embodiment, the boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres prepared above are used for boron extraction from salt lakes. The application process includes the following steps:
[0098] (1) Adsorption and regeneration process: The prepared boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were packed into a fixed-bed adsorption column. The brine feed flow rate was controlled at 20 BV / h, and the adsorption time was 2h to dynamically adsorb and enrich boron. After adsorption saturation, a 0.5mol / L hydrochloric acid solution was used as the regenerator. The regeneration flow rate was 5 BV / h, and the regeneration time was 1h to complete the desorption of boron and the regeneration of the adsorbent. The regenerated adsorbent was directly recycled for the next round of brine boron extraction without additional activation treatment. This process yielded an eluent with a concentration of 20-40 g / L.
[0099] (2) Evaporation and concentration process: The eluent is placed in a triple-effect evaporator for evaporation and crystallization at a temperature of 90°C for 3 hours. Water and hydrogen chloride gas are evaporated and then condensed and recovered using a condenser to obtain hydrochloric acid solution for reuse as a regenerator. This process yields a concentrated solution of 200-250 g / L.
[0100] (3) Cooling and crystallization process: The concentrated liquid is slowly cooled from high temperature at a rate of 4℃ / h (too fast a cooling rate will form fine crystals, increasing the difficulty of solid-liquid separation). The solid-liquid mixture is centrifuged and the solid is dried in an oven at 40℃ to obtain boric acid crystals. The mother liquor can be recycled.
[0101] The physical image and electron microscope image of the obtained boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres are shown below. Figure 3 , Figure 4 As shown, the boron adsorbent microspheres synthesized in this embodiment have relatively uniform size, and the electron micrograph shows that there are a large number of three-dimensional network pore structures on the surface of the microsphere particles, which is beneficial to improving the efficiency of the adsorption and desorption process.
[0102] Table 1 shows the composition of the original brine of a certain Dong XXX Salt Lake, with a boron content of 0.85 g / L. This actual water body was used as the adsorption influent. The total boron concentration was tested in the mixed permeate after adsorption, and the boron adsorption capacity was calculated based on the boron concentrations of the influent and permeate. The measured boron adsorption capacity is shown in Table 2, which is 59.3 g / L, far exceeding that of commercially available meglumine-type boron adsorption resin (11 g / L under the same conditions). This indicates that the boron adsorbent synthesized in this embodiment has the advantage of high adsorption capacity. In addition, the total concentration of sulfate and chloride ions in the eluent is very low, at 17 mg / L (under the same conditions, the total concentration of sulfate and chloride ions in the eluent of commercially available meglumine-type boron adsorption resin is 347 mg / L), proving that the boron extraction process of the boron adsorbent is not affected by the high concentration of sulfate and chloride ions in the original brine system, and can be used for direct boron extraction from original brine of salt lakes. Furthermore, by treating adsorption and desorption as a single cycle, it was found that during acid regeneration (using inductively coupled plasma atomic emission spectrometry (ICP) to test the content of titanium, lanthanum, and cerium), these elements were undetectable. After 300 cycles, the adsorption capacity decreased by only 1.4%, a rate significantly lower than that of commercially available meglumine-type boron adsorption resins (which experience a 37.2% decrease under the same conditions), demonstrating the excellent cyclic stability of this boron adsorbent. The regenerated solution was placed in a triple-effect evaporator for evaporation and concentration, followed by cooling and crystallization. The resulting solid boric acid had a purity of 99.8% (compared to 96.4% for commercially available meglumine-type boron adsorption resins under the same conditions), proving that this method can yield high-purity boric acid products.
[0103] Example 2
[0104] In this Example 2, a method for synthesizing boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres is provided. The synthesis method includes the following steps:
[0105] (1) Preparation of composite lignin OK-Lignin: Organic solvent lignin (O-Lignin) and sulfate lignin (K-Lignin) were weighed at a mass ratio of 1:3. The weighed O-Lignin and K-Lignin lignin powders were put into a high-speed pulverizer and mechanically pulverized at 5000 rpm for 10 min to ensure thorough physical mixing of the two lignins. The pulverized material was passed through a 100-mesh standard sieve (sieve hole diameter 0.150 mm), and the sieved material was collected for later use. The sieved mixed lignin was placed in a vacuum drying oven and dried at an absolute vacuum of ≤-0.08 MPa and a temperature of 70℃ for 6 h to remove adsorbed free water and low-boiling-point volatile impurities from the lignin, resulting in dried OK-Lignin powder.
[0106] (2) Preparation of TiO(OH)2-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 2 mol / L titanium oxysulfate (TiOSO4) solution and stirred for 30 min. 4 mol / L sodium carbonate solution was added dropwise to the solution to adjust the pH to 7. The generated metatitanic acid was uniformly deposited on the lignin network surface as nano-sized particles. The mixture was filtered, the filter cake was washed with deionized water, dried at 70 °C, and then pulverized to obtain TiO(OH)2-OK-Lignin powder.
[0107] (3) Preparation of La(OH)3-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 2 mol / L lanthanum chloride LaCl3·7H2O solution and stirred for 30 min. 4 mol / L sodium carbonate solution was added dropwise to the solution to adjust the pH to 9. The generated La(OH)3 particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried at 70 °C, and then pulverized to obtain La(OH)3-OK-Lignin powder.
[0108] (4) Preparation of Ce(OH)4-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 2 mol / L cerium-rich Ce(SO4)2 solution and stirred for 30 min. 4 mol / L sodium hydroxide solution was added dropwise to the solution to adjust the pH to 11. The generated Ce(OH)4 particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried at 70 °C, and then pulverized to obtain Ce(OH)4-OK-Lignin powder.
[0109] (5) Preparation of OK-Lignin-PVB organic adhesive: 1 kg of OK-Lignin powder and 2 kg of polyvinyl butyral with an acetal degree of 40%-45% were added to 30 kg of dimethylacetamide (DMAC) solvent, heated to 70°C, and stirred for 10 h to obtain a uniform OK-Lignin-PVB-DMAC organic adhesive.
[0110] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: TiO(OH)2-OK-Lignin, La(OH)3-OK-Lignin, and Ce(OH)4-OK-Lignin were weighed in a mass ratio of 1:1:1.5. The three powders were put into a high-speed rotary granulator and mechanically mixed at 2000 rpm for 20 min to ensure thorough physical mixing. Then, OK-Lignin-PVB-DMAC adhesive was added at a glue-to-powder ratio of 0.6:1 and granulated at 1000 rpm for 16 min to obtain microspheres with a particle size of 1.5 mm. The microspheres were placed in a 60℃ oven to evaporate the DMAC solvent, resulting in TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres.
[0111] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Epichlorohydrin (ECH) and anhydrous ethanol were mixed and diluted at a volume ratio of 1:5 to obtain a homogeneous solution. 10 kg of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres were placed in a reaction vessel, and 20 kg of ECH ethanol solution was added. The cross-linking reaction was carried out at 80 °C for 5 h, so that the epoxy groups of ECH and some phenolic hydroxyl and alcohol hydroxyl groups on the lignin and PVB molecular chains underwent ring-opening etherification reaction to form a covalent cross-linked network. The surface and interior of the microspheres were cleaned with deionized water to remove residual ECH and ethanol, and TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were obtained.
[0112] In this embodiment, the boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres prepared above are used for boron extraction from salt lakes, including the following steps:
[0113] (1) Adsorption and regeneration process: The prepared boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were packed into a fixed-bed adsorption column. The brine feed flow rate was controlled at 40 BV / h, and the adsorption time was 3h to dynamically adsorb and enrich boron. After adsorption saturation, a 2.5mol / L hydrochloric acid solution was used as the regenerator. The regeneration flow rate was 15 BV / h, and the regeneration time was 2h to complete the desorption of boron and the regeneration of the adsorbent. The regenerated adsorbent was directly recycled for the next round of brine boron extraction without additional activation treatment. This process yielded an eluent with a concentration of 20-40 g / L.
[0114] (2) Evaporation and concentration process: The eluent is placed in a triple-effect evaporator for evaporation and crystallization. The evaporation temperature is 110℃ and the evaporation time is 5h. Water and hydrogen chloride gas are evaporated and then condensed and recovered through a condenser to obtain hydrochloric acid solution for reuse as a regenerator. This process yields a concentrated solution of 200-250g / L.
[0115] (3) Cooling and crystallization process: The concentrated liquid is slowly cooled from high temperature at a rate of 10℃ / h (too fast a cooling rate will form fine crystals, increasing the difficulty of solid-liquid separation). The solid-liquid mixture is centrifuged and the solid is dried in an oven at 50℃ to obtain boric acid crystals. The mother liquor can be recycled.
[0116] The physical image and electron microscope image of the obtained boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres are shown below. Figure 5 , Figure 6 As shown, the boron adsorbent microspheres synthesized in this embodiment have relatively uniform size, and the electron micrograph shows that there are a large number of three-dimensional network pore structures on the surface of the microsphere particles, which is beneficial to improving the efficiency of the adsorption and desorption process.
[0117] Table 1 shows the composition of the original brine of DongXXX Salt Lake, with a boron content of 0.85 g / L. This actual water body was used as the adsorption influent. The total boron concentration was tested in the mixed permeate after adsorption, and the boron adsorption capacity was calculated based on the boron concentrations of the influent and permeate. The measured boron adsorption capacity is shown in Table 2, which is 62.3 g / L, far exceeding that of commercially available meglumine-type boron adsorption resin (11 g / L under the same conditions). This indicates that the boron adsorbent synthesized in this embodiment has the advantage of high adsorption capacity. In addition, the total concentration of sulfate and chloride ions in the eluent is very low, at 22 mg / L (under the same conditions, the total concentration of sulfate and chloride ions in the eluent of commercially available meglumine-type boron adsorption resin is 347 mg / L), proving that the boron extraction process of the boron adsorbent is not affected by the high concentration of sulfate and chloride ions in the original brine system, and can be used for direct boron extraction from original brine of salt lakes. Furthermore, by treating adsorption and desorption as a single cycle, it was found that during acid regeneration (using inductively coupled plasma atomic emission spectrometry (ICP) to test the content of titanium, lanthanum, and cerium), these elements were undetectable. After 300 cycles, the adsorption capacity decreased by only 1.7%, a rate significantly lower than that of commercially available meglumine-type boron adsorption resins (which experience a 37.2% decrease under the same conditions), demonstrating the excellent cyclic stability of this boron adsorbent. The regenerated solution was placed in a triple-effect evaporator for evaporation and concentration, followed by cooling and crystallization. The resulting solid boric acid had a purity of 99.7% (compared to 96.4% for commercially available meglumine-type boron adsorption resins under the same conditions), proving that this method can yield high-purity boric acid products.
[0118] Example 3
[0119] In this embodiment 3, a method for synthesizing boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres is first provided. The synthesis method includes the following steps:
[0120] (1) Preparation of composite lignin OK-Lignin: Organic solvent lignin (O-Lignin) and sulfate lignin (K-Lignin) were weighed at a mass ratio of 1:2. The weighed O-Lignin and K-Lignin lignin powders were put into a high-speed pulverizer and mechanically pulverized at 4000 rpm for 7.5 min to ensure thorough physical mixing of the two lignins. The pulverized material was passed through a 100-mesh standard sieve (sieve hole diameter 0.150 mm), and the sieve-undersized material was collected for later use. The sieved mixed lignin was placed in a vacuum drying oven and dried at an absolute vacuum of ≤-0.08 MPa and a temperature of 60℃ for 5 h to remove adsorbed free water and low-boiling-point volatile impurities from the lignin, resulting in dried OK-Lignin powder.
[0121] (2) Preparation of TiO(OH)2-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1.5 mol / L titanium oxysulfate (TiOSO4) solution and stirred for 20 min. 3 mol / L sodium carbonate solution was added dropwise to the solution to adjust the pH to 6. The generated metatitanic acid was uniformly deposited on the surface of the lignin network as nano-sized particles. The mixture was filtered, the filter cake was washed with deionized water, dried at 60 °C, and then pulverized to obtain TiO(OH)2-OK-Lignin powder.
[0122] (3) Preparation of La(OH)3-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1.5 mol / L lanthanum chloride LaCl3·7H2O solution and stirred for 20 min. 3 mol / L sodium carbonate solution was added dropwise to the solution to adjust the pH to 8.5. The generated La(OH)3 particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried at 60 °C, and then pulverized to obtain La(OH)3-OK-Lignin powder.
[0123] (4) Preparation of Ce(OH)4-OK-Lignin: 1 kg of dry OK-Lignin powder was placed in 2 L of 1.5 mol / L cerium sulfate Ce(SO4)2 solution and stirred for 20 min. 3 mol / L sodium hydroxide solution was added dropwise to the solution to adjust the pH to 10. The generated Ce(OH)4 particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried at 60 °C, and then pulverized to obtain Ce(OH)4-OK-Lignin powder.
[0124] (5) Preparation of OK-Lignin-PVB organic adhesive: 1 kg of OK-Lignin powder and 1.5 kg of polyvinyl butyral with an acetal degree of 40%-45% were added to 25 kg of dimethylacetamide (DMAC) solvent, heated to 60°C, and stirred for 7.5 h to obtain a uniform OK-Lignin-PVB-DMAC organic adhesive.
[0125] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: TiO(OH)2-OK-Lignin, La(OH)3-OK-Lignin, and Ce(OH)4-OK-Lignin were weighed in a mass ratio of 1:1:1. The three powders were put into a high-speed rotary granulator and mechanically mixed at 1500 rpm for 15 min to ensure thorough physical mixing. Then, OK-Lignin-PVB-DMAC adhesive was added at a glue-to-powder ratio of 0.5:1 and granulated at 750 rpm for 12 min to obtain microspheres with a particle size of 0.7-1.5 mm. The microspheres were placed in a 50℃ oven to evaporate the DMAC solvent, resulting in TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres.
[0126] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Epichlorohydrin (ECH) and anhydrous ethanol were mixed and diluted at a volume ratio of 1:4 to obtain a homogeneous solution. 10 kg of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres were placed in a reaction vessel, and 15 kg of ECH ethanol solution was added. The reaction was carried out at 70 °C for 4 h to allow the epoxy groups of ECH to undergo ring-opening etherification with some phenolic and alcoholic hydroxyl groups on the lignin and PVB molecular chains, forming a covalent cross-linked network. The surface and interior of the microspheres were cleaned with deionized water to remove residual ECH and ethanol, thus obtaining TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres.
[0127] In this embodiment, a method for extracting boron from salt lakes using the boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres prepared above is described. The method includes:
[0128] (1) Adsorption and regeneration process: The prepared boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres were packed into a fixed-bed adsorption column. The brine feed flow rate was controlled at 30 BV / h, and the adsorption time was 2.5h to dynamically adsorb and enrich boron. After adsorption saturation, a 1.5mol / L hydrochloric acid solution was used as the regenerator. The regeneration flow rate was 10 BV / h, and the regeneration time was 1.5h to complete the desorption of boron and the regeneration of the adsorbent. The regenerated adsorbent was directly recycled for the next round of brine boron extraction without additional activation treatment. This process yielded an eluent with a concentration of 20-40 g / L.
[0129] (2) Evaporation and concentration process: The eluent is placed in a triple-effect evaporator for evaporation and crystallization. The evaporation temperature is 100℃ and the evaporation time is 4h. Water and hydrogen chloride gas are evaporated and then condensed and recovered through a condenser to obtain hydrochloric acid solution for reuse as a regenerator. This process yields a concentrated solution of 200-250g / L.
[0130] (3) Cooling and crystallization process: The concentrated liquid is slowly cooled from high temperature at a rate of 7℃ / h (too fast a cooling rate will form fine crystals, increasing the difficulty of solid-liquid separation). The solid-liquid mixture is centrifuged and the solid is dried in an oven at 45℃ to obtain boric acid crystals. The mother liquor can be recycled.
[0131] The physical image and electron microscope image of the obtained boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres are shown below. Figure 7 , Figure 8 As shown, the boron adsorbent microspheres synthesized in this invention have relatively uniform size, and the electron micrographs show that the surface of the microsphere particles has a large number of three-dimensional network pore structures, which is beneficial to improving the efficiency of the adsorption and desorption process.
[0132] Table 1 shows the composition of the original brine of DongXXX Salt Lake, with a boron content of 0.85 g / L. This actual water body was used as the adsorption influent. The total boron concentration was tested in the mixed permeate after adsorption, and the boron adsorption capacity was calculated based on the boron concentrations of the influent and permeate. In this embodiment, the measured boron adsorption capacity is shown in Table 2, which is 65.2 g / L, far exceeding that of commercially available meglumine-type boron adsorption resin (11 g / L under the same conditions). This indicates that the boron adsorbent synthesized in this invention has the advantage of high adsorption capacity. In addition, the total concentration of sulfate and chloride ions in the eluent is very low, at 27 mg / L (under the same conditions, the total concentration of sulfate and chloride ions in the eluent of commercially available meglumine-type boron adsorption resin is 347 mg / L), proving that the boron extraction process of the boron adsorbent is not affected by the high concentration of sulfate and chloride ions in the original brine system, and can be used for direct boron extraction from the original brine of salt lakes. Furthermore, by treating adsorption and desorption as a single cycle, it was found that during acid regeneration (using inductively coupled plasma atomic emission spectrometry (ICP) to test the content of titanium, lanthanum, and cerium), these elements were undetectable. After 300 cycles, the adsorption capacity decreased by only 1.9%, a rate significantly lower than that of commercially available meglumine-type boron adsorption resins (which experience a 37.2% decrease under the same conditions), demonstrating the excellent cyclic stability of this boron adsorbent. The regenerated solution was placed in a triple-effect evaporator for evaporation and concentration, followed by cooling and crystallization. The resulting solid boric acid had a purity of 99.6% (compared to 96.4% for commercially available meglumine-type boron adsorption resins under the same conditions), proving that this method can yield high-purity boric acid products.
[0133] Comparative Example 1
[0134] In Comparative Example 1, a method for synthesizing boron adsorbent microspheres is provided, the method comprising:
[0135] (1) Preparation of O-Lignin: Only organic solvent lignin (O-Lignin) is used as raw material, and sulfate lignin (K-Lignin) is not used. The specific method is the same as in Example 1.
[0136] (2) Preparation of TiO(OH)2-O-Lignin: Same as in Example 1.
[0137] (3) Preparation of La(OH)3-O-Lignin: Same as in Example 1.
[0138] (4) Preparation of Ce(OH)4-O-Lignin: Same as in Example 1.
[0139] (5) Preparation of O-Lignin-PVB organic adhesive: Same as in Example 1.
[0140] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-O-Lignin-PVB microspheres: Same as in Example 1.
[0141] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-O-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0142] The difference between the boron adsorbent synthesis method of Comparative Example 1 and Example 1 is that the preparation of the composite lignin OK-Lignin in Example 1 is a composite lignin matrix, that is, a combination of organic solvent lignin O-Lignin and sulfate lignin K-Lignin, not a single lignin. Comparative Example 1 only uses organic solvent lignin (O-Lignin) as raw material, without sulfate lignin (K-Lignin).
[0143] The adsorption capacity of the boron adsorbent in Comparative Example 1, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 41.7 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 31 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 19.3%, a much higher rate than in Example 1, demonstrating poor cycling stability of this boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid was 99.1%, showing little change compared to Example 1. Therefore, compared to Example 1, the boron adsorbent in Comparative Example 1 mainly exhibits a decrease in adsorption capacity and worse cycling stability.
[0144] The reason is that the lignin used is a water-insoluble composite lignin matrix, namely, a combination of organic solvent lignin O-Lignin and sulfate lignin K-Lignin. It is not a single lignin, and does not contain lignin sulfonate, tannic acid, or any water-soluble modifying groups. The beneficial effects are as follows: Organic solvent lignin (O-Lignin) is extracted by organic solvent method, has a relatively low molecular weight (Mw1000-3000Da), a high phenolic hydroxyl content (about 3.5-5.0 mmol / g), contains abundant guaiac and syringyl structural units, has good flexibility, is easy to disperse in alkaline medium, and provides a large number of uniform anchoring sites for inorganic nanoparticles; Sulfate lignin (K-Lignin) is obtained from the by-product of sulfate pulping, has a high molecular weight (Mw3000-8000Da), contains more condensed structural units and aliphatic hydroxyl groups, has strong rigidity, and can provide excellent mechanical strength and structural stability for composite adsorbents. When O-Lignin and K-Lignin are combined, O-Lignin provides high-density hydroxyl anchoring sites and good dispersibility, while K-Lignin provides rigid support and structural stability. The two complement each other, forming a "flexible-rigid" synergistic organic framework structure, which is beneficial for improving adsorption capacity and cycling stability.
[0145] Comparative Example 2
[0146] In Comparative Example 2, a method for synthesizing boron adsorbent microspheres is provided, comprising:
[0147] (1) Preparation of K-Lignin: Only sulfate lignin (K-Lignin) was used as the raw material, and organic solvent lignin (O-Lignin) was not used. The specific method was the same as in Example 1.
[0148] (2) Preparation of TiO(OH)2-K-Lignin: Same as in Example 1.
[0149] (3) Preparation of La(OH)3-K-Lignin: Same as in Example 1.
[0150] (4) Preparation of Ce(OH)4-K-Lignin: Same as in Example 1.
[0151] (5) Preparation of K-Lignin-PVB organic adhesive: Same as in Example 1.
[0152] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-K-Lignin-PVB microspheres: Same as in Example 1.
[0153] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-K-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0154] The difference between the boron adsorbent synthesis method of Comparative Example 2 and Example 1 is that the preparation of the composite lignin OK-Lignin in Example 1 is a composite lignin matrix, that is, a combination of organic solvent lignin O-Lignin and sulfate lignin K-Lignin, not a single lignin. Comparative Example 2 only uses sulfate lignin (K-Lignin) as raw material, without organic solvent lignin (O-Lignin).
[0155] The adsorption capacity of the boron adsorbent in Comparative Example 2, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 23.5 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 28 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 3.5%, a slightly higher rate than in Example 1, demonstrating good cyclic stability of the boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid was 99.2%, showing little change compared to Example 1. Therefore, the main difference between the boron adsorbent in Comparative Example 2 and Example 1 lies in the decrease in adsorption capacity.
[0156] The reason is that the lignin used is a water-insoluble composite lignin matrix, namely, a combination of organic solvent lignin O-Lignin and sulfate lignin K-Lignin. It is not a single lignin, and does not contain lignin sulfonate, tannic acid, or any water-soluble modifying groups. The beneficial effects are as follows: Organic solvent lignin (O-Lignin) is extracted by organic solvent method, has a relatively low molecular weight (Mw1000-3000Da), a high phenolic hydroxyl content (about 3.5-5.0 mmol / g), contains abundant guaiac and syringyl structural units, has good flexibility, is easy to disperse in alkaline medium, and provides a large number of uniform anchoring sites for inorganic nanoparticles; Sulfate lignin (K-Lignin) is obtained from the by-product of sulfate pulping, has a high molecular weight (Mw3000-8000Da), contains more condensed structural units and aliphatic hydroxyl groups, has strong rigidity, and can provide excellent mechanical strength and structural stability for composite adsorbents. When O-Lignin and K-Lignin are combined, O-Lignin provides high-density hydroxyl anchoring sites and good dispersibility, while K-Lignin provides rigid support and structural stability. The two complement each other, forming a "flexible-rigid" synergistic organic framework structure, which is beneficial for improving adsorption capacity and cycling stability.
[0157] Comparative Example 3
[0158] In Comparative Example 3, a method for synthesizing boron adsorbent microspheres is provided, comprising:
[0159] (1) Preparation of composite lignin OK-Lignin: Same as in Example 1.
[0160] (2) Preparation of TiO(OH)2-OK-Lignin: This operation is not required.
[0161] (3) Preparation of La(OH)3-OK-Lignin: Same as in Example 1.
[0162] (4) Preparation of Ce(OH)4-OK-Lignin: Same as in Example 1.
[0163] (5) Preparation of OK-Lignin-PVB organic adhesive: Same as in Example 1.
[0164] (6) Preparation of La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: Same as in Example 1.
[0165] (7) Preparation of La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0166] The difference between the boron adsorbent synthesis method of Comparative Example 3 and Example 1 is that Example 1 has the step of "preparation of TiO(OH)2-OK-Lignin", while Comparative Example 3 does not have this step, that is, TiO(OH)2 is missing from the effective components of the boron adsorbent.
[0167] The adsorption capacity of the boron adsorbent in Comparative Example 3, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 17.2 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 23 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 2.3%, a slightly higher rate than in Example 1, demonstrating good cyclic stability of the boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid is 99.5%, showing little change compared to Example 1. Therefore, the main difference between the boron adsorbent in Comparative Example 3 and Example 1 lies in the decrease in adsorption capacity.
[0168] The reason lies in the fact that the boron adsorbent uses inorganic components containing dihydroxy metatitanic acid, trihydroxy lanthanum hydroxide, and tetrahydroxy cerium hydroxide as its inorganic components, rather than a single species of inorganic component. The beneficial effects are: metatitanic acid (TiO(OH)2, 2 hydroxyl groups): structurally stable and resistant to acids and alkalis, precisely adapting to small-molecule neutral boric acid H3BO3 in salt lakes, forming a stable five-membered ring complex, achieving efficient capture of small-molecule boron; lanthanum hydroxide (La(OH)3, 3 hydroxyl groups): a highly acid and alkali resistant rare earth hydroxide with a stable trihydroxy stereocoagulation structure, precisely adapting to monopolyboronate B(OH)4. -This significantly enhances the selective adsorption capacity of monoboron; cerium hydroxide (Ce(OH)4, with four hydroxyl groups): its tetrahydroxy multi-site structure exhibits strong coordination ability, specifically suited to high-molecular-weight polyboron anions, achieving stable adsorption of macromolecular polyboron through multi-site cross-linking. A 2 / 3 / 4-membered gradient hydroxyl synergistic system is constructed, comprehensively covering the adsorption of all boron species in salt lakes, completely overcoming the technical bottleneck of traditional adsorbents that can only adsorb a single boron species. It breaks through the upper limits of adsorption capacity and selectivity caused by traditional single-site adsorbents, and all components are resistant to the acid-alkali and high-salt environments of salt lakes, exhibiting extremely strong structural stability and significantly improving adsorption capacity and selectivity.
[0169] Comparative Example 4
[0170] In Comparative Example 4, a method for synthesizing boron adsorbent microspheres is provided, comprising:
[0171] (1) Preparation of composite lignin OK-Lignin: Same as in Example 1.
[0172] (2) Preparation of TiO(OH)2-OK-Lignin: Same as in Example 1.
[0173] (3) Preparation of La(OH)3-OK-Lignin: This operation is not required.
[0174] (4) Preparation of Ce(OH)4-OK-Lignin: Same as in Example 1.
[0175] (5) Preparation of OK-Lignin-PVB organic adhesive: Same as in Example 1.
[0176] (6) Preparation of TiO(OH)2-Ce(OH)4-OK-Lignin-PVB microspheres: Same as in Example 1.
[0177] (7) Preparation of TiO(OH)2-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0178] The difference between the boron adsorbent synthesis method of Comparative Example 4 and Example 1 is that Example 1 has the step of "preparation of La(OH)3-OK-Lignin", while Comparative Example 4 does not have this step, that is, the effective component of the boron adsorbent lacks La(OH)3.
[0179] The adsorption capacity of the boron adsorbent in Comparative Example 4, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 14.8 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 19 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 2.0%, a slightly higher rate than in Example 1, demonstrating good cyclic stability of the boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid is 99.4%, showing little change compared to Example 1. Therefore, the main difference between the boron adsorbent in Comparative Example 4 and Example 1 lies in the decrease in adsorption capacity.
[0180] The reason is that the boron adsorbent in Example 1 uses inorganic components containing dihydroxy metatitanic acid, trihydroxy lanthanum hydroxide, and tetrahydroxy cerium hydroxide, instead of a single-species inorganic component. The beneficial effects are: metatitanic acid (TiO(OH)2, 2 hydroxyl groups): structurally stable and resistant to acids and alkalis, precisely adapting to small-molecule neutral boric acid H3BO3 in salt lakes, forming a stable five-membered ring complex, achieving efficient capture of small-molecule boron; lanthanum hydroxide (La(OH)3, 3 hydroxyl groups): a highly acid and alkali resistant rare earth hydroxide with a stable trihydroxy stereocoagulation structure, precisely adapting to monopolyboronate B(OH)4. - This significantly enhances the selective adsorption capacity of monoboron; cerium hydroxide (Ce(OH)4, with four hydroxyl groups): its tetrahydroxy multi-site structure exhibits strong coordination ability, specifically suited to high-molecular-weight polyboron anions, achieving stable adsorption of macromolecular polyboron through multi-site cross-linking. A 2 / 3 / 4-membered gradient hydroxyl synergistic system is constructed, comprehensively covering the adsorption of all boron species in salt lakes, completely overcoming the technical bottleneck of traditional adsorbents that can only adsorb a single boron species. It breaks through the upper limits of adsorption capacity and selectivity caused by traditional single-site adsorbents, and all components are resistant to the acid-alkali and high-salt environments of salt lakes, exhibiting extremely strong structural stability and significantly improving adsorption capacity and selectivity.
[0181] Comparative Example 5
[0182] In Comparative Example 5, a method for synthesizing boron adsorbent microspheres is provided, the method comprising:
[0183] (1) Preparation of composite lignin OK-Lignin: Same as in Example 1.
[0184] (2) Preparation of TiO(OH)2-OK-Lignin: Same as in Example 1.
[0185] (3) Preparation of La(OH)3-OK-Lignin: Same as in Example 1.
[0186] (4) Preparation of Ce(OH)4-OK-Lignin: This operation is not required.
[0187] (5) Preparation of OK-Lignin-PVB organic adhesive: Same as in Example 1.
[0188] (6) Preparation of TiO(OH)2-La(OH)3-OK-Lignin-PVB microspheres: Same as in Example 1.
[0189] (7) Preparation of TiO(OH)2-La(OH)3-OK-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0190] The difference between the boron adsorbent synthesis method of Comparative Example 5 and Example 1 is that Example 1 has the step of "preparation of Ce(OH)4-OK-Lignin", while Comparative Example 5 does not have this step, that is, Ce(OH)4 is missing from the effective components of the boron adsorbent.
[0191] The adsorption capacity of the boron adsorbent in Comparative Example 5, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 23.6 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 24 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 2.2%, a slightly higher rate than in Example 1, demonstrating good cyclic stability of the boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid is 99.2%, showing little change compared to Example 1. Therefore, the main difference between the boron adsorbent in Comparative Example 5 and Example 1 lies in the decrease in adsorption capacity.
[0192] The reason is that the boron adsorbent in Example 1 uses inorganic components containing dihydroxy metatitanic acid, trihydroxy lanthanum hydroxide, and tetrahydroxy cerium hydroxide, instead of a single-species inorganic component. The beneficial effects are: metatitanic acid (TiO(OH)2, 2 hydroxyl groups): structurally stable and resistant to acids and alkalis, precisely adapting to small-molecule neutral boric acid H3BO3 in salt lakes, forming a stable five-membered ring complex, achieving efficient capture of small-molecule boron; lanthanum hydroxide (La(OH)3, 3 hydroxyl groups): a highly acid and alkali resistant rare earth hydroxide with a stable trihydroxy stereocoagulation structure, precisely adapting to monopolyboronate B(OH)4. - This significantly enhances the selective adsorption capacity of monoboron; cerium hydroxide (Ce(OH)4, with four hydroxyl groups): its tetrahydroxy multi-site structure exhibits strong coordination ability, specifically suited to high-molecular-weight polyboron anions, achieving stable adsorption of macromolecular polyboron through multi-site cross-linking. A 2 / 3 / 4-membered gradient hydroxyl synergistic system is constructed, comprehensively covering the adsorption of all boron species in salt lakes, completely overcoming the technical bottleneck of traditional adsorbents that can only adsorb a single boron species. It breaks through the upper limits of adsorption capacity and selectivity caused by traditional single-site adsorbents, and all components are resistant to the acid-alkali and high-salt environments of salt lakes, exhibiting extremely strong structural stability and significantly improving adsorption capacity and selectivity.
[0193] Comparative Example 6
[0194] In Comparative Example 6, a method for synthesizing boron adsorbent microspheres is provided, the method comprising:
[0195] (1) Preparation of lignin OK-Lignin: Same as in Example 1.
[0196] (2) Preparation of TiO(OH)2-OK-Lignin: Same as in Example 1.
[0197] (3) Preparation of La(OH)3-OK-Lignin: Same as in Example 1.
[0198] (4) Preparation of Ce(OH)4-OK-Lignin: Same as in Example 1.
[0199] (5) Preparation of OK-Lignin-PVB organic adhesive: High acetal degree (80%) PVB is used as the organic adhesive, and PVB with an acetal degree of 40%-45% is not used as the raw material. Other operations are the same as in Example 1.
[0200] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: Same as in Example 1.
[0201] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0202] The difference between the synthesis method of boron adsorbent in Comparative Example 6 and Example 1 is that Example 1 uses PVB with an acetal degree of 40%-45% as raw material, while Comparative Example 6 uses PVB with a high acetal degree (80%) as organic adhesive.
[0203] The adsorption capacity of the boron adsorbent in Comparative Example 6, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 46.2 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 26 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 28.7%, a much higher rate than in Example 1, demonstrating poor cycling stability of this boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid was 99.3%, showing little change compared to Example 1. Therefore, compared to Example 1, the main differences in the boron adsorbent of Comparative Example 6 are a decrease in adsorption capacity and a deterioration in cycling stability.
[0204] The reason is that polyvinyl butyral with an acetalization degree of 40%-45% is used as an organic adhesive. In addition to using lignin as an organic adhesive, polyvinyl butyral with an acetalization degree of 40%-45% is also used as an organic binder instead of high acetalization degree (80%) PVB. The beneficial effects are as follows: PVB with an acetalization degree of 40%-45% is a low acetalization degree PVB. This molecular structure contains a large number of hydroxyl groups. These hydroxyl groups have two main functions. The first function is that they can adsorb boron elements. While acting as an adhesive, they can also achieve boron extraction, thereby increasing the total boron extraction capacity of the boron adsorbent TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres. The second function is that they can chemically crosslink with epichlorohydrin (ECH) together with lignin. Using ECH, PVB and lignin are chemically crosslinked together to form a more stable spatial network organic framework structure, ensuring that the microspheres have high mechanical strength and high porosity.
[0205] Comparative Example 7
[0206] Comparative Example 7 provides a method for synthesizing boron adsorbent microspheres, the method comprising:
[0207] (1) Preparation of lignin OK-Lignin: Same as in Example 1.
[0208] (2) Preparation of TiO(OH)2-OK-Lignin: Same as in Example 1.
[0209] (3) Preparation of La(OH)3-OK-Lignin: Same as in Example 1.
[0210] (4) Preparation of Ce(OH)4-OK-Lignin: Same as in Example 1.
[0211] (5) Preparation of PVB organic adhesive: Only PVB is used as the organic adhesive, and OK-Lignin is not used as the organic adhesive. Other operations are the same as in Example 1.
[0212] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: Same as in Example 1.
[0213] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0214] The difference between the boron adsorbent synthesis method of Comparative Example 7 and Example 1 is that Example 1 uses OK-Lignin and PVB as composite organic adhesives, while Comparative Example 7 only uses PVB as an organic adhesive.
[0215] The adsorption capacity of the boron adsorbent in Comparative Example 7, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 48.6 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 25 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 39.8%, a much higher rate than in Example 1, demonstrating the poor cycling stability of this boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid was 99.7%, showing little change compared to Example 1. Therefore, compared to Example 1, the main differences in the boron adsorbent of Comparative Example 7 are a decrease in adsorption capacity and a deterioration in cycling stability.
[0216] The reason is that, in addition to using PVB as the core component, OK-Lignin was also added as a core component when formulating the organic adhesive. The beneficial effect of using OK-Lignin plus PVB dual adhesive is that, by adding extra OK-Lignin to the organic adhesive, the OK-Lignin that mainly functions as an adhesive will not occupy the OK-Lignin in the three core components of TiO(OH)2-OK-Lignin, La(OH)3-OK-Lignin, and Ce(OH)4-OK-Lignin. This helps maintain the binding stability and interaction force between TiO(OH)2, La(OH)3, and Ce(OH)4 and OK-Lignin in the three core components of TiO(OH)2-OK-Lignin, La(OH)3, and Ce(OH)4-OK-Lignin, ensuring the dispersibility and adsorption performance of the three effective components of TiO(OH)2, La(OH)3, and Ce(OH)4.
[0217] Comparative Example 8
[0218] In Comparative Example 8, a method for synthesizing boron adsorbent microspheres is provided, the synthesis method comprising:
[0219] (1) Preparation of lignin OK-Lignin: Same as in Example 1.
[0220] (2) Preparation of TiO(OH)2-OK-Lignin: Same as in Example 1.
[0221] (3) Preparation of La(OH)3-OK-Lignin: Same as in Example 1.
[0222] (4) Preparation of Ce(OH)4-OK-Lignin: Same as in Example 1.
[0223] (5) Preparation of PVB organic adhesive: Same as in Example 1.
[0224] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: Same as in Example 1.
[0225] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: This operation is not required.
[0226] The difference between the synthesis method of boron adsorbent in Comparative Example 8 and Example 1 is that Example 1 uses epichlorohydrin to crosslink and cure PVB and OK-Lignin, while Comparative Example 8 does not have this operation.
[0227] The adsorption capacity of the boron adsorbent in Comparative Example 8, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 41.2 g / L, indicating a significant decrease compared to Example 1. The total concentration of sulfate and chloride ions in the eluent is very low, at 27 mg / L, showing little change compared to Example 1. Furthermore, after 300 cycles, the adsorption capacity decreased by 52.8%, a much higher rate than in Example 1, demonstrating poor cycling stability of this boron adsorbent. After evaporation, concentration, and cooling crystallization, the purity of the obtained solid boric acid was 99.5%, showing little change compared to Example 1. Therefore, compared to Example 1, the main differences in the boron adsorbent of Comparative Example 8 are a decrease in adsorption capacity and a deterioration in cycling stability.
[0228] The reason is that without cross-linking and curing, a large amount of inorganic active ingredients are lost, and the cycle stability drops sharply. ECH is used for cross-linking reaction: the biepoxy groups of epichlorohydrin form covalent bridges between lignin and PVB molecular chains, cross-linking lignin and PVB together and transforming them into a three-dimensional network structure that is completely insoluble in water. At the same time, inorganic nanoparticles are firmly anchored in the organic framework, which completely solves the technical problems of water solubility loss and inorganic powder detachment of traditional lignin-based adsorbents.
[0229] Comparative Example 9
[0230] This comparative example provides a method for synthesizing boron adsorbent microspheres, the method comprising:
[0231] (1) Preparation of lignin OK-Lignin: Same as in Example 1.
[0232] (2) Preparation of TiO(OH)2-OK-Lignin: Same as in Example 1.
[0233] (3) Preparation of La(OH)3-OK-Lignin: Same as in Example 1.
[0234] (4) Preparation of Ce(OH)4-OK-Lignin: Same as in Example 1.
[0235] (5) Preparation of PVB organic adhesive: Same as in Example 1.
[0236] (6) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-PVB microspheres: Same as in Example 1.
[0237] (7) Preparation of TiO(OH)2-La(OH)3-Ce(OH)4-OK-Lignin-ECH-PVB microspheres: Same as in Example 1.
[0238] In this comparative example, the boron adsorbent microspheres prepared above are used for boron extraction from salt lakes, including:
[0239] (1) Adsorption and regeneration process: A hydrochloric acid solution with a concentration of 4 mol / L was used as the regenerator, and other operations were the same as in Example 1.
[0240] (2) Evaporation and concentration process: Same as in Example 1.
[0241] (3) Cooling crystallization process: Same as in Example 1.
[0242] The difference between the boron adsorbent application method in Comparative Example 9 and Example 1 is that Example 1 uses a 0.5 mol / L hydrochloric acid solution as a regenerator, while Comparative Example 9 uses a high-concentration 4 mol / L hydrochloric acid solution as a regenerator.
[0243] The adsorption capacity of the boron adsorbent in Comparative Example 9, measured according to the method of Example 1, is shown in Table 2. The boron adsorption capacity is 59.3 g / L. The total concentration of sulfate and chloride ions in the eluent is very low, at 17 mg / L. Taking adsorption and desorption as a cycle, it was found that during acid regeneration (the content of titanium, lanthanum, and cerium was measured by inductively coupled plasma atomic emission spectrometry (ICP)), the concentrations of titanium, lanthanum, and cerium were 156 mg / L, 202 mg / L, and 113 mg / L, respectively. Furthermore, after 300 cycles, the adsorption capacity decreased by 89.7%, a rate much higher than that in Example 1, indicating that the acid used during regeneration had seriously exceeded the allowable acidity limit, and the boron adsorbent exhibited poor cycle stability under these regeneration conditions. After evaporation, concentration, and cooling crystallization of the eluent, the purity of the obtained solid boric acid was 82.5%, which is very low. It can be seen that compared with Example 1, the boron adsorbent in Comparative Example 9 mainly exhibits decreased cycle stability and low boron purity.
[0244] The reason is that using a hydrochloric acid solution with a concentration of 0.5-2.5 mol / L as the regenerator in the regeneration process has the following advantages: if the acid concentration is too low, it will lead to excessive acidification solution usage, excessively long regeneration time, and low regeneration efficiency; if the acid concentration is too high, it will cause severe acid erosion of the boron adsorbent's chemical framework, resulting in severe chemical dissolution of the material, irreversible damage, and a significant decrease in cycle stability. Using an appropriate acid concentration for regeneration helps protect the structural stability of the boron adsorbent and improves the stability of its engineering operation.
[0245] Table 1
[0246]
[0247] Table 2
[0248]
[0249] While the specific embodiments of the present invention have been described above in conjunction with the accompanying drawings, this is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that, based on the technical solutions disclosed in the present invention, various modifications or variations that can be made by those skilled in the art without creative effort should be included within the scope of protection of the present invention.
Claims
1. A method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine, characterized in that, include: Weigh out organic solvent lignin and sulfate lignin, put them into a high-speed pulverizer and pulverize them to fully mix the two types of lignin; sieve the pulverized material. The sieved mixed lignin was placed in a vacuum drying oven and dried at a constant temperature to remove the adsorbed free water and low-boiling-point volatile impurities from the lignin, thus obtaining dried composite lignin powder. Dry composite lignin powder was placed in a titanium sulfate solution and stirred to disperse it. Sodium carbonate solution was added dropwise to adjust the pH of the solution to 5-7. The generated metatitanic acid particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, and the filter cake was dried and pulverized to obtain metatitanic acid composite lignin powder. Dry composite lignin powder was placed in a lanthanum chloride solution and stirred to disperse it. Sodium carbonate solution was added dropwise to the solution to adjust the pH to 8-9. The resulting lanthanum hydroxide particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, and the filter cake was dried and pulverized to obtain lanthanum hydroxide composite lignin powder. The composite lignin powder was placed in a cerium sulfate solution and stirred to disperse it. Sodium hydroxide solution was added dropwise to the solution to adjust the pH value to 9-11. The resulting cerium hydroxide particles were uniformly deposited on the surface of the lignin network. The mixture was filtered, the filter cake was washed with deionized water, dried and crushed to obtain cerium hydroxide composite lignin powder. Composite lignin powder and polyvinyl butyral were added to dimethylacetamide solvent, heated, and stirred to obtain a uniform organic adhesive. Weigh out the metatitanic acid composite lignin powder, lanthanum hydroxide composite lignin powder and cerium hydroxide composite lignin powder and put them into a high-speed rotary granulator to fully mix the three powders physically; add the organic adhesive according to the ratio to granulate and obtain small balls; place the small balls in an oven to evaporate the solvent. Epichlorohydrin was mixed and diluted with anhydrous ethanol to obtain a homogeneous solution. The microspheres were placed in a reaction vessel, and the homogeneous solution was added. The reaction was carried out under heat to induce a cross-linking reaction, which caused the epoxy groups in epichlorohydrin to undergo ring-opening etherification with some of the phenolic and alcoholic hydroxyl groups on the molecular chains of lignin and polyvinyl butyral, forming a covalent cross-linked network. The surface and interior of the microspheres were cleaned with deionized water to remove residual epichlorohydrin and ethanol, thus obtaining boron adsorbent microspheres.
2. The method for synthesizing and preparing the boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, Weigh organic solvent lignin and sulfate lignin at a mass ratio of 1:1-3; place the sieved mixed lignin in a vacuum drying oven and dry it at a constant temperature of 50-70℃ under absolute vacuum conditions ≤-0.08 MPa to remove adsorbed free water and low-boiling-point volatile impurities from the lignin, and obtain dried composite lignin powder.
3. The method for synthesizing and preparing the boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, 1 kg of dry composite lignin powder was placed in 2 L of 1-2 mol / L titanium oxysulfate solution and stirred to disperse. 2-4 mol / L sodium carbonate solution was added dropwise to the solution and the pH of the solution was adjusted to 5-7. The resulting metatitanic acid particles were uniformly deposited on the surface of the lignin network.
4. The method for synthesizing and preparing the boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, 1 kg of dry composite lignin powder was placed in 2 L of 1-2 mol / L lanthanum chloride solution and stirred to disperse. 2-4 mol / L sodium carbonate solution was added dropwise to the solution, and the pH of the solution was adjusted to 8-9. The resulting lanthanum hydroxide particles were uniformly deposited on the surface of the lignin network.
5. The method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, 1 kg of dry composite lignin powder was placed in 2 L of 1-2 mol / L cerium sulfate solution and stirred to disperse. 2-4 mol / L sodium hydroxide solution was added dropwise to the solution to adjust the pH to 9-11. The resulting cerium hydroxide particles were uniformly deposited on the surface of the lignin network.
6. The method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, Add 1 kg of composite lignin powder and 1-2 kg of polyvinyl butyral with an acetal content of 40%-45% to 20-30 kg of dimethylacetamide (DMAC) solvent, heat to 50-70℃, and stir for 5-10 hours to obtain a uniform organic adhesive.
7. The method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, Weigh out the metatitanic acid composite lignin powder, lanthanum hydroxide composite lignin powder, and cerium hydroxide composite lignin powder in a mass ratio of 1:1:0.5-1.
5.
8. The method for synthesizing and preparing the boron adsorbent for boron extraction from salt lake brine according to claim 7, characterized in that, The three powders were weighed and put into a high-speed rotary granulator for mechanical mixing to ensure thorough physical mixing. An organic adhesive was added at a ratio of 0.4-0.6:1, and the mixture was then rotary granulated.
9. The method for synthesizing and preparing a boron adsorbent for boron extraction from salt lake brine according to claim 1, characterized in that, Epichlorohydrin and anhydrous ethanol are mixed and diluted at a volume ratio of 1:3-5 to obtain a homogeneous solution. 10 kg of small balls are placed in a reaction vessel, and 10-20 kg of the homogeneous solution is added. The reaction is carried out at 60-80℃ for crosslinking.
10. The application of the boron adsorbent prepared by the preparation method according to any one of claims 1-9 in boron extraction from salt lake brine, characterized in that, include: (1) Adsorption and regeneration process: The prepared boron adsorbent spheres are packed into a fixed bed adsorption column. The brine feed flow rate is controlled at 20-40 BV / h and the adsorption time is 2-3h to dynamically adsorb and enrich boron. After adsorption saturation, a hydrochloric acid solution with a concentration of 0.5-2.5mol / L is used as a regenerator. The regeneration flow rate is 5-15 BV / h and the regeneration time is 1-2h to complete the desorption of boron and the regeneration of the adsorbent. The regenerated adsorbent is directly recycled for the next round of brine boron extraction without additional activation treatment. This process yields an eluent with a concentration of 20-40g / L. (2) Evaporation and concentration process: The eluent is placed in a triple-effect evaporator for evaporation and crystallization. The evaporation temperature is 90-110℃ and the evaporation time is 3-5h. The water and hydrogen chloride gas are evaporated and condensed and recovered by a condensation device to obtain hydrochloric acid solution for reuse as a regenerator. This process yields a concentrated solution of 200-250g / L. (3) Cooling and crystallization process: The concentrated liquid is slowly cooled from high temperature at a rate of 4-10℃ / h; the solid-liquid mixture is centrifuged and the solid is dried in an oven at 40-50℃ to obtain boric acid crystals. The mother liquor can be recycled.
